A Brief Analysis of the Application of English Language in British and American Literature Based on Artificial Intelligence. Issue 2 (May 2021) - An, Kun
Abstract: artificial intelligence (AI), abbreviated in English, is the research and development of human body to produce new technologies to simulate and expand the application of human intelligence in machines. The ultimate goal of artificial intelligence is to be able to produce robots that are not different from human beings and only listen to human beings. To achieve this technology, the most important thing is to be able to analyze and study the substantive operation function of human intelligence. The most ideal way of language learning is to be able to personally visit the language environment, feel the atmosphere of the language culture, and have in-depth communication with the language owner. However, in reality, such an idealized state is impossible to exist, so literary works have become more ideal language and cultural materials. Both British and American languages use English to communicate, although both belong to English, the cultural differences lead to their different ways of expression. This paper first makes a simple analysis of the artificial intelligence system, then analyzes the differences between British and American literary works, and then interprets and analyzes the application of artificial intelligence system in British and American literary works in detail.